(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2025)
The quality of health services greatly affects patient satisfaction, including maternity care. This study aims to analyze the relationship between the quality of maternity services and maternal satisfaction at TK III Dr. Bratanata Hospital in Jambi. A quantitative approach with a cross-sectional design was used. A sample of 68 respondents was selected using purposive sampling from a total population of 978 maternity patients. Data were collected via questionnaires and analyzed using the correlation matrix algorithm in AI Studio 2024.0.3. The results revealed that empathy (r=0.392), responsiveness (r=0.359), reliability (r=0.216), tangibles (r=0.204), and assurance (r=0.020) are associated with maternity service satisfaction. The F-test also showed a significant effect between service quality and maternal satisfaction (F=14.0599; p<0.05). These findings highlight the need for continuous soft skills training for medical personnel and improvements in maternity service workflows.